An investigation of the apprenticeship organisational socialization strategy - Blau, Gary [Verfasser] (My University, 1988)
"Using a sample of new employees from an insurance company, this study tested specific hypotheses regarding the apprenticeship socialization strategy. Perceived quality of intern-assignment manager work relationship, measured from multiple perspectives, was found to have an important direct and moderating effect on intern work outcomes. Quality of work relationship was significantly positively related to intern met expectations, role clarity, organizational commitment, and performance, and it moderated the relationship between role clarity and performance." (author's abstract) ((en)) Die Sozialisation von Lehrlingen wird am Beispiel eines Versicherungsunternehmens untersucht. Dabei wird insbesondere auf die Qualität der Arbeitsbeziehungen eingegangen. (IAB)
Untersuchung der Sozialisation von Lehrlingen
Keywords: G 1.2.4.2.4 Kredit und Versicherung; G 2.3.1 Arbeitsteilung & -organisation; G 2.3 Wandel von Arbeit & Wirtschaft; G 2.4 Sozialer Wandel; Versicherungsgewerbe; Berufliche Sozialisation; Auszubildender; Berufsrolle; Verhalten; Quantitative Angaben